Governance for Handling Fake News: Structural Modeling Approach - Andriansyah, Azis; Makarim, Edmon; Sucahyo, Yudho Giri; Setyobudi, Chairul Muriman (Universitas Dharma Wacana, 2023)
The main aim of this research was to evaluate the effectiveness of government intervention in addressing the issue of Internet-based fake news, which poses a significant threat to national security. The study utilized statistical methods and employed a survey approach to gather data from a sample population. Simple random sampling was used as the sampling technique, and interviews were conducted with selected individuals who had relevant insights from organizations such as the national police, BSSN, Kemenkominfo, and BIN. The collected data was analyzed using the Partial Least Square (PLS) model with the assistance of the WarpPLS package.The findings of the study indicated a strong correlation between effective governance in combating the spread of fake news and the enhancement of national resilience. This implies that implementing robust and strategic governance practices is crucial for fostering a resilient nation. The study emphasizes the importance of government intervention in countering Internet-based fake news to protect national security. By addressing this issue effectively, governments can contribute to the overall resilience of the nation. The research highlights the significance of proactive measures and informed decision-making in tackling the challenges posed by fake news in the digital era